The impact of complex ecosystems in the food industry - Chorna, Olha (Видавництво Національного університету “Львівська політехніка”, 2024)
Today, in food safety, one of the most difficult to identify by visual methods, without accredited methodological practices, is microbiological contamination, which carries a risk of product quality reduction and a high risk of consumer poisoning by pathogenic microorganisms. This type of contamination can pose a significant threat to the health of the consumer and incur both reputational and financial losses for the manufacturer. In a highly competitive food manufacturing environment, manufacturers must pay attention to the risks that affect them.
Keywords: Microbiology; Food industry; Sanitary treatment; Threat to consumer health; prevention of the development of resistance of microorganisms